IMPLEMENTATION OF THE BASIC PRINCIPLES OF GREEN BANKING IN CORPORATE GOVERNANCE - KRASNOVA, Iryna; DVORNYK, Iryna; LAVRENIUK, Vladyslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of implementation of green banking principles in corporate governance of banks in the context of global climate and social challenges. The key principles of green banking - transparency, integration of ESG principles, risk management, environmental responsibility, innovation, government support, social responsibility, financial inclusion, crisis resilience and international cooperation - and their impact on sustainable economic growth are considered. Particular attention is paid to the Ukrainian context, where military challenges, limited regulatory framework and low stakeholder awareness complicate the implementation of green practices. Based on international experience (ING Bank, Deutsche Bank, Banco do Brasil) and generalisation of the practice of Ukrainian banks (Ukrgasbank, Oschadbank, PrivatBank), the author proposes tools for integrating ESG criteria, including financial (green loans, bonds), managerial (ESG strategies), regulatory, technological (AI, blockchain) and communication mechanisms. Attention is focused on the need to harmonise Ukrainian legislation with European standards (EU Taxonomy) and strengthen cooperation with international organisations (EBRD, IFC) to support post-war reconstruction and green economic transformation. The article offers recommendations for improving the regulatory framework, staff training and expanding access to green financial products for vulnerable groups, which will contribute to sustainable development and integration of Ukraine into the global market.
Keywords: green banking; ESG criteria; corporate governance; sustainable development; risk management; social responsibility; economic growth; financing; post-war reconstruction; Ukraine; EU Taxonomy; European integration; bank; international organisations; loan portfolio; financial instruments